2014
DOI: 10.1021/jf503682j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Six Chinese Spices on Heterocyclic Amine Profiles in Roast Beef Patties by Ultra Performance Liquid Chromatography-Tandem Mass Spectrometry and Principal Component Analysis

Abstract: The effects of Chinese spices on the profiles of 17 heterocyclic amines (HAs) from seven HA categories were investigated in roast beef patties using Ultra Performance Liquid Chromatography-Tandem Mass Spectrometry (UPLC-MS/MS) and principal component analysis. Three groups of HAs, imidazopyridines (PhIP, DMIP, and 1,5,6-TMIP), imidazoquinoxalines (MeIQx and 4,8-DiMeIQx), and β-carbolines (harman and norharman), were detected and quantified in all of the samples. The results demonstrated that the total HA and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 28 publications
(50 reference statements)
4
36
1
Order By: Relevance
“…For the samples of precursors without and with naringenin (Fig. 1b, c) [14]. Moreover, the precision values for HAs in the present work are in agreement with previously reported values [23,24].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…For the samples of precursors without and with naringenin (Fig. 1b, c) [14]. Moreover, the precision values for HAs in the present work are in agreement with previously reported values [23,24].…”
Section: Resultssupporting
confidence: 93%
“…Precursors with or without the addition of 0.018 g (0.03, 0.06, 0.06, 0.07, 0.12, 0.11, 0.09 and 0.05 mmol of rutin, luteolin, quercetin, naringenin, protocatechuic acid, p-coumaric acid, ferulic acid and chlorogenic acid, respectively) of a test flavonoid or phenolic acid were mixed with 8 mL diethylene glycol in screw cap-sealed glass tubes, and the total volumes were 10 mL by adding water. The temperature meter of the oil bath heating block was set to 230 °C according to previous study on beef patties [14] and preheated until equilibrium before inserting the tubes into the cavities. The heating time was 20 min after the equilibrium, and fluctuation of temperature was within 2 °C.…”
Section: Formation and Extraction Of Has In Chemical Model Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary, several studies have found that natural herbs/spices/antioxidants may promote PhIP formation in cooked foods. For example, Zeng and others () reported that adding 1% cumin, chili, or black pepper into roasted beef patties significantly increased PhIP formation by 52%, 33%, or 45%. A mixture of basil (0.5%), coriander (0.2%), and sweet grass (0.2% to 0.5%) extracts was also reported to increase the concentration of PhIP in cooked beef samples (Damašiusa and others ).…”
Section: Introductionmentioning
confidence: 99%